Hørindustriens Tilstand i Randers Omegn i de 2 Aar fra 1ste Junii 1836 til ult. Mai 1838. - Blicher, S. S. (Tidsskrift for Landøkonomi, 2018)
Hørindustriens Tilstand i Randers Omegn i de 2 Aar fra 1ste Junii 1836 til ult. Mai 1838.